2014
DOI: 10.14814/phy2.12198
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes maintain greater fluorescent bile acid accumulation and greater sensitivity to drug-induced cell death in three-dimensional matrix culture

Abstract: Primary hepatocytes undergo phenotypic dedifferentiation upon isolation from liver that typically includes down regulation of uptake transporters and up regulation of efflux transporters. Culturing cells between layers of collagen in a three‐dimensional (3D) “sandwich” is reported to restore hepatic phenotype. This report examines how 3D culturing affects accumulation of fluorophores, the cytotoxic response to bile acids and drugs, and whether cell to cell differences in fluorescent anion accumulation correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several hypotheses may reflect this result. It may be due to (i) a reduction of the cell viability, (ii) either a reduction of the esterase activity and weaker functionality of those enzymes (iii) or a weaker transport of the compound by the hepatic transporter in the cells due to the differentiation [23,24]. In the present study, additional viability using the trypan blue assay and the continuous basal metabolism check points (glucose, albumin, urea analyses over time) showed that the reduction of calcein signals was not due to cell death (although viability was low in biochips on day 5, similar results were found on days 9 and 13).…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses may reflect this result. It may be due to (i) a reduction of the cell viability, (ii) either a reduction of the esterase activity and weaker functionality of those enzymes (iii) or a weaker transport of the compound by the hepatic transporter in the cells due to the differentiation [23,24]. In the present study, additional viability using the trypan blue assay and the continuous basal metabolism check points (glucose, albumin, urea analyses over time) showed that the reduction of calcein signals was not due to cell death (although viability was low in biochips on day 5, similar results were found on days 9 and 13).…”
Section: Discussionmentioning
confidence: 99%
“…The model was capable to metabolize carboxydichlorofluorescein diacetate (CDFDA) by hepatic esterase(C.-J. Lin et al 2016) and its bioproduct, a fluorescent compound called carboxydichlorofluorescein (CDF) accumulated in the bile and was excreted into the bile canaliculi similarly to in vivo (Nakao et al 2011) (Murray, Han, and Wolkoff 2014). This result is a good example that demonstrates how replicating the bioarchitecture of tissue can restore organ in vivo functions, including metabolic pathways, maintaining cellular phenotype, tissue polarity, bio-synthetic and transportation ability of tissues(F. M. Chen and Liu 2016).…”
Section: Microfluidic Devicesmentioning
confidence: 99%